2017
DOI: 10.1007/s40261-017-0508-1
|View full text |Cite
|
Sign up to set email alerts
|

Initiation, Switching, and Cessation of Psoriasis Treatments Among Patients with Moderate to Severe Psoriasis in the United States

Abstract: Based on health claims data, undertreatment of moderate to severe psoriasis appeared to be common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…This study examined treatment patterns among psoriasis patients over a period longer than 12 months, enabling us to show that all of the examined outcomes became progressively worse over time, from 12 to 24 months. Our findings add to the growing literature indicating that adherence and persistence with the currently used biologics and apremilast may be problematic over the long term (17,18), particularly in patients with metabolic conditions (14)(15)(16).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This study examined treatment patterns among psoriasis patients over a period longer than 12 months, enabling us to show that all of the examined outcomes became progressively worse over time, from 12 to 24 months. Our findings add to the growing literature indicating that adherence and persistence with the currently used biologics and apremilast may be problematic over the long term (17,18), particularly in patients with metabolic conditions (14)(15)(16).…”
Section: Discussionsupporting
confidence: 59%
“…Long-term real-world treatment patterns are not wellcharacterized in psoriasis, with the majority of US studies only considering the first 12 months after treatment initiation (17,18). In particular, comparative treatment patterns in patients with and without metabolic conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…According to other studies, and emphasised in the current German S3 Guidelines for psoriasis and chronic spontaneous urticaria, biologicals should be used in treatment refractory, moderate to severe psoriasis and chronic spontaneous urticaria . Although many studies showed a cost‐effectiveness advantage, only a minority of patients are treated in accordance with these guidelines, and an undertreatment of moderate to severe psoriasis seems to be very common . Even though there is a positive trend in the usage of systemic therapies, this issue has to be addressed to improve psoriasis health care nationwide, with an emphasis on including rural areas, as proposed by the World Health Organisation (WHO) in their Global Psoriasis Report .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Although many studies showed a cost-effectiveness advantage, only a minority of patients are treated in accordance with these guidelines, 2,[13][14][15][16][17] and an undertreatment of moderate to severe psoriasis seems to be very common. 18 Even though there is a positive trend in the usage of systemic therapies, 19 this issue has to be addressed to improve psoriasis health care nationwide, with an emphasis on including rural areas, as proposed by the World Health Organisation (WHO) in their Global Psoriasis Report. 16,19,20 In this context, the WHO also stresses the need for improvement of health service research and research on barriers hindering guideline-compliant treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy with topical steroids and topical vitamin A or D compounds is superior to either therapy alone [3]. However, topical therapies are commonly discontinued due to expense and inconvenience of continued application, especially in moderate to severe forms of psoriasis [5]. An alternative to topical therapies is oral, subcutaneous or intravenous immunomodulators and biologics.…”
Section: Introductionmentioning
confidence: 99%